New Geographical Regionalization of Russia - V. A. Gorbanyov (Vestnik MGIMO-Universiteta)
After the October Revolution there was an urgent need for a new economic zoning of Russia. Under the leadership of the greatest scientists the Soviet Union was divided in to economic regions. After the collapse of the USSR and the emergence of a market economy, these regions have lost their meaning, and the new were not created. Therefore there was a need of a new zoning Russia, and not by economic regions, but by the complex geographical regions. This is a difficult task, but because of the author's opinion that geography should be a single, new geographical areas should reflect their historical, natural, economic, social, cultural view specifics. This approach will promote rational geographical division of labor in the country in a market economy. An attempt to new geographical zoning, with 10 allocated geographic regions: Capital, Central, European North, European South, North Caucasus, Volga-Urals, Western Siberia, Southern Siberia, Northern Siberia and the Far East. For each region area, population size and density, level of urbanization, natural, mechanical and overall population growth, GDP per capita, the structure of employment, Human Development Index were counted, and the appropriate analysis were made.